O estado da arte da produção científica em educação especial na Biblioteca Virtual em Saúde (BVS) : um estudo bibliométrico - Pizzani, Luciana (2008)
Special Education approach and its interfaces with other knowledge areas are evidenced through the diverse scientific production consolidated in scientific journals besides national and international databases. In the present work, a bibliometric analysis of Special Education scientific production was done in the databases of the Virtual Health Library (VHL), coordinated by BIREME a specialized center of the Pan American Health Organization, which promotes the dissemination and use of scientific information in health. The proposed methodology was developed in four phases, namely: a) literature review on special education and bibliometrics to theoretically support the research; b) data collection in the bases LILACS, MEDLINE, BBO, BDENF, MEDCARIB, PAHO and WHOLIS; c) organization and bibliometric treatment of the collected data by using the software Vantage Point and MS Excel for bibliometric analysis besides preparation of graphs and tables; d) result analysis, recovering exposed concepts in the theoretical pattern to support the obtained data analyses and interpretations. The following bibliometric indicators were produced in the Medline basis: English is the predominant language; most of the records had individual authorship; the record type is scientific paper; the predominant descriptor was Special Education; the main theme in journals was Medicine; and the most frequent country was The United States. As regards the databases LILACS, BBO, BDENF, MEDCARIB, PAHO, and WHOLIS, the indicators were represented as follows: Portuguese was the predominant language; most records had individual authorship; the predominant type is the original paper; the main themes were Special Education, People presenting disabilities, mental retardation, Brazil, mental handicap education, people presenting impaired hearing, Education, Learning, Rehabilitation, Rehabilitation Centers, Hearing Education and Disorders; the mostly found themes in journals were psychology and development psychology, and the country with the largest number of records is Brazil. Results indicated the interface among Health Sciences, Information Science and Special Education, which allowed viewing of the state of the art in Special Education in the VHL databases, besides contributing to the dissemination of these databases to researchers in the field as an important scientific information source.